BUSINESS PROCESS MODELLING PADA DIVISI PUBLIC RELATION PERGURUAN TINGGI - Dede Wira Trise Putra; Ayra Priyanka (Program Studi Teknik Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an, 2023)
Public relations division is part of a company or organization that is responsible for preparing special communication plans with various media in an effort to build an image and good and beneficial relations between the organization and the public. Some of these public relations jobs are related to public communications such as managing incoming and outgoing mail. This research was conducted to design new business processes in the development of current business processes. Where the problem to be solved is a problem in terms of time. The business process flow will be described with the Business Process Modeling And Notation (BPMN) modeling technique. The research was carried out in several stages, namely data collection, information, literature study, analysis of the old process flow and business flow analysis of the recommendation process. Based on the research conducted, it was found that the new business process flow can speed up the processing time for the completion of incoming and outgoing letters. With the time analysis of this business process, the stages of work on the tasks of each section can be known in the form of time estimates that accelerate the business process of managing letters in the public relation division.